1999
DOI: 10.1111/j.1349-7006.1999.tb00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations in Ulcerative Colitis‐associated Neoplasia Focusing on APC, K‐ras Gene and Microsatellite Instability

Abstract: The status of genetic alterations in ulcerative colitis (UC)-associated neoplasia (UCAN) was investigated focusing on microsatellite instability (MSI) which is seen in a certain fraction of colorectal carcinomas, and adenomatous polyposis coli (APC) gene and K-ras gene, in which mutations occur in the early stage of sporadic colorectal tumorigenesis. Thirty-one UCAN from 15 UC patients who had undergone colorectal resection at our institution were investigated. There were 8 lesions of invasive carcinoma, 15 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 39 publications
(56 reference statements)
1
46
0
Order By: Relevance
“…Flat adenomas have been characterized as an important precursor to colorectal carcinoma (Rembacken et al, 2000). These lesions have a low frequency of Kras gene mutation (Jass, 1995), as does dysplasia complicating chronic inflammatory bowel disease in the form of ulcerative colitis and Crohn colitis, in which MSI-H is relatively common (Umetani et al, 1999). Our finding that K-ras gene mutation is infrequent in Egyptian colorectal carcinomas unassociated with schistosomiasis raises the possibility that the flat adenoma could be an important precursor.…”
Section: Discussionmentioning
confidence: 79%
“…Flat adenomas have been characterized as an important precursor to colorectal carcinoma (Rembacken et al, 2000). These lesions have a low frequency of Kras gene mutation (Jass, 1995), as does dysplasia complicating chronic inflammatory bowel disease in the form of ulcerative colitis and Crohn colitis, in which MSI-H is relatively common (Umetani et al, 1999). Our finding that K-ras gene mutation is infrequent in Egyptian colorectal carcinomas unassociated with schistosomiasis raises the possibility that the flat adenoma could be an important precursor.…”
Section: Discussionmentioning
confidence: 79%
“…MGMT methylation may not serve as a [29] maker to predict premalignant condition in non-neoplastic-looking mucosa in UC. Some studies have reported the relationship between MSI status and UC-associated CRC [15,28]. A high incidence of the MSI in long-standing UC with severe inflammation probably reflects genomic instability caused by repeated inflammation stress [15].…”
Section: Discussionmentioning
confidence: 98%
“…However, the reported frequency of MSI-H has varied from 9 to 50%. 17,20,21 MSI has also been reported in colorectal epithelium of UC patients suffering from chronic inflammation. 16,18,19 Importantly, most of the reported microsatellite analysis has been undertaken on bulk samples of either the tumor or nonmalignant epithelium and, thus, the status of MSI-H could be due to the pooling effect of individual microfoci which showed MSI(-L) in different markers.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] In lesions undergoing chronic inflammation, microsatellite instability (MSI) is a possible genetic alteration, and high-and low-level of MSI (MSI-H and MSI-L) has been described in UC associated neoplasm (UCAN). [16][17][18][19][20][21][22][23] However, the reported frequency of MSI-H, a consequence of a defective mismatch repair (MMR) system (notably MLH1 or MSH2), and MSI-L, a consequence in part of O 6 -methylguanine-DNA methyltransferase (MGMT) deficiency, 24 has varied considerably from 9 to 50%, and 11 to 85%, respectively. 22,[25][26][27] In situation of considerable genetic heterogeneity within a sample, collection of samples without microdissection could possibly obscure the findings of MSI.…”
mentioning
confidence: 99%